EFEK PELATIHAN KEMAMPUAN PENYUSUNAN PERANGKAT PERCOBAAN SAINS UNTUK OPTIMALISASI CTL - Istiyono, Edi; Wilujeng, Insih (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2015)
Activity   of  service   community   have  objects:   (1)  after  upgrading, partie Sainsnts  have   a skill to use of science  equipment  needed  of CTL,  (2) partie  Sainsnts   have     a  skill  to  use,  plan,  and  make  science   equipment needed  of CTL,  (3) partie  Sainsnts  have  a skill  to complete  the  equipment with work sheet,  (4) partie  Sainsnts  have   a skill to make science  equipment from second-hand  materialThe   activity    is   explaining,    information-discussion,     work   group,workshop  and experiment.   The activity  is carried  out classical  and group  for24  hour.  The  activity   is  explaining,   discussion,   topic  choosing   that  are continued  work group  and presentation.Based  on observation   can  be concluded:  (1) increase  of skill  to use of science  equipment   needed  of CTL,  (2) increase  of skill  to use,  plan,  and make  science   equipment    needed   of  CTL,  (3)  particSainsnts    have   made science  equipment   completed   with  work  sheet,  and  (4) particSainsnts   have had a skill to make  science  equipment  from second-hand  material.